2006
DOI: 10.1055/s-2005-921189
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of PillCam ESO Capsule Endoscopy Versus Conventional Upper Endoscopy for the Diagnosis of Esophageal Varices: A Prospective Three-Center Pilot Study

Abstract: In a high-prevalence population, PillCam ESO may represent an accurate noninvasive alternative to EGD for the detection of esophageal varices and portal hypertensive gastropathy. A large-scale trial is underway to validate and expand these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 10 publications
3
79
0
5
Order By: Relevance
“…A procedure that may replace EGD is esophageal capsule endoscopy. Two recent pilot studies show that capsule endoscopy is a safe and well-tolerated way to diagnose esophageal varices, 47,48 although its sensitivity remains to be established. Thus, capsule endoscopy may play a future role in screening for esophageal varices if additional larger studies support its use.…”
Section: Diagnosis Of Varices and Variceal Hemorrhagementioning
confidence: 99%
“…A procedure that may replace EGD is esophageal capsule endoscopy. Two recent pilot studies show that capsule endoscopy is a safe and well-tolerated way to diagnose esophageal varices, 47,48 although its sensitivity remains to be established. Thus, capsule endoscopy may play a future role in screening for esophageal varices if additional larger studies support its use.…”
Section: Diagnosis Of Varices and Variceal Hemorrhagementioning
confidence: 99%
“…Fifty-one articles were excluded after review of the titles and abstracts, leaving 30 articles for detailed evaluation by two independent reviewers. Of these, five met our inclusion criteria [10,[14][15][16][17] . Two studies were identified by hand search in DDW 2008 meeting abstracts and reference lists respectively [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…Recent years, a number of studies have been performed for evaluating CE in diagnosing esophageal disease, especially for Barrett's esophagus and esophageal varices, and the results varied [8][9][10] . If CE is a definitive diagnostic tool for esophageal varices, it is necessary to evaluate whether CE is sufficiently accurate for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modalities such as platelet count, platelet count to spleen diameter ratio, and fibroscan could have a good predictive value but need confirmation by further studies. Capsule endoscopy has emerged as a new diagnostic tool and is considered safe and well tolerated, although its sensitivity remains to be established [15,16]. Its role for screening varices needs further studies.…”
Section: Definitions Of Varices and Variceal Bleed Prophylaxismentioning
confidence: 99%